2017
DOI: 10.18801/jbar.120117.122
|View full text |Cite
|
Sign up to set email alerts
|

Yield and leaf nutrient concentrations of common bean genotypes as influenced by aluminium toxicity under acidic soils

Abstract: The study was carried out to assess the effect of different concentrations of exchangeable aluminum on yield and nutrient concentrations in the leaf tissues of two common bean genotypes grown in pots on limed and unlimed acidic soils. Factorial combinations of five aluminum rates and two common bean genotypes were laid out in a completely randomized design with three replications. Yield and leaf nutrient concentrations were markedly affected by aluminium application and the magnitude of this effect depended on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
1
Order By: Relevance
“…Similar findings were reported by Kushwaha et al (2017) in cowpea. Legesse et al (2017) also reported a significant decrease in plant height with aluminium treatment in common bean.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar findings were reported by Kushwaha et al (2017) in cowpea. Legesse et al (2017) also reported a significant decrease in plant height with aluminium treatment in common bean.…”
Section: Resultsmentioning
confidence: 88%
“…From the results obtained, it was revealed that marked negative effects of aluminium were observed at higher aluminium levels. Effect of interaction between genotypes and aluminium treatment were found to be significant as Legesse et al (2017) reported significant reductions in the pod length and yield of common bean in response to applying higher level of aluminium (100 mg Al/ kg soil), however at the lower rate (12.5 mg Al/kg soil), they observed no significant difference for all the yield components compared to the control. In agreement with the results of this study, Kushwaha et al (2017) reported a decrease in pod weight and pod yield in response to aluminium treatment in soil.…”
Section: Genotypesmentioning
confidence: 91%
“…Con respecto al K, de acuerdo a Das et al (2019), este elemento es requerido por los cultivos casi en las mismas proporciones o en algunos casos mayor que el N; no obstante, la mayoría de los agricultores solo aplican N, o N y P sin considerar o solo agregando cantidades pequeñas de fertilizante potásico. Esto concuerda con los resultados en los Cuadros 2, 3 y 4, con bajos contenidos de K y elevadas concentraciones de P. Con relación a sitios de pH ácido, Legesse et al (2017) mencionan que la acidif icación del suelo resulta en la def iciencia de nutrientes, entre ellos el K. Diversos estudios han demostrado que la disponibilidad de K es menor en suelos ácidos (Zhang et al, 2009), lo cual reduce el rendimiento de los cultivos. Por esta razón, corregir la acidez de los sitios evaluados resulta un factor importante en la asimilación de los nutrientes por los cultivos, en el caso del K, Liu et al (2020) mencionan que la adición de cal permite remover el Al de los sitios intercambiables incrementando la disponibilidad de K y otras bases intercambiables.…”
Section: Resultados Y Discusiónunclassified
“…Therefore, statisticians and breeders are continuously putting effort to develop an effective model to select superior genotypes based on multiple traits. In this regard, initially genotype by trait (GT) analysis was proposed to understand the relationship among traits and genotypes (Yan and Rajcan 2002) and was utilized by many breeders in cereals as well as in other crops (Rubio et al 2004;Oladejo et al 2011;Legesse et al 2013;Paramesh et al 2016). However, this GT biplot model cannot show the strengths and weaknesses of a genotype, hence deprives of providing a decisive power of selection or rejection of given genotype (Yan et al 2019).…”
Section: Selection Of the Best Genotype Based On Multiple Traitsmentioning
confidence: 99%